Suicide from a socio-legal perspective in the first half of the 19th century on Polish lands under Russian occupation - Rozental, Przemysław (Requiem, 2025)
The issue of suicide throughout history is an interesting phenomenon from a legal perspective. It raises the question whether it is possible to punish a dead criminal effectively? In the perspective of penal codifications operating in the lands of the Kingdom of Poland under Russian rule, there are provisions that actually concern this issue. Using the deductive method and linguistic interpretation of the provisions of criminal law applicable in Polish lands under the Russian partition, it is possible to present the criminal law issue of suicide as a crime not only of a moral nature but also of a factual nature.